Greater Left Inferior Frontal Activation for SVO than VOS during Sentence Comprehension in Kaqchikel - Koizumi, Masatoshi; Kim, Jungho (Frontiers in Psychology, 2016)
Cortical activations during the processing of sentences with different word orders in Kaqchikel were investigated using functional magnetic resonance imaging. Kaqchikel is an endangered Mayan language spoken in Guatemala. The word order in this language is relatively flexible. We observed higher cortical activations in the left inferior frontal gyrus for sentences with the subject-verb-object (SVO) word order, as compared to sentences with the verb-object-subject (VOS) word order, suggesting that VOS is easier to process than SVO. This supports the traditional interpretation in Mayan linguistics that the syntactically simplest word order of transitive sentences is VOS in Kaqchikel, as in many other Mayan languages. More importantly, the results revealed that the subject-before-object word order preference in sentence comprehension, observed in a number of previous studies on other languages, might not reflect a universal aspect of human languages; rather, processing preference may be language-specific to some extent, reflecting syntactic differences in individual languages.